Coating synthesis controlled by electron-beam heating; IOP Conference Series: Materials Science and Engineering; Vol. 140 : Interdisciplinary Problems in Additive Technologies - Gordienko A. I. Anatoly Illarionovich (2016, 2016)
Title screen